Locust Bean Gum Nano-Based Hydrogel for Vaginal Delivery of Diphenyl Diselenide in the Treatment of Trichomoniasis: Formulation Characterization and In Vitro Biological Evaluation - Fernanda Padoin dos Reis; Graziela Vargas Rigo; Cristina Wayne Nogueira; Tiana Tasca; Marcel Henrique Marcondes Sari; Letícia Cruz (MDPI AG, 2022)
Trichomoniasis is the most common nonviral sexually transmitted infection in the world, but its available therapies present low efficacy and high toxicity. Diphenyl diselenide (PhSe2) is a pharmacologically active organic selenium compound; however, its clinical use is hindered by its lipophilicity and toxicity. Nanocarriers are an interesting approach to overcome the limitations associated with this compound. This study designed and evaluated a vaginal hydrogel containing PhSe2-loaded Eudragit® RS100 and coconut oil nanocapsules for the treatment of trichomoniasis. Nanocapsules presented particle sizes in the nanometric range, positive zeta potential, a compound content close to the theoretical value, and high encapsulation efficiency. The nanoencapsulation maintained the anti-Trichomonas vaginalis action of the compound while improving the scavenger action in a DPPH assay. The hydrogels were prepared by thickening nanocapsule suspensions with locust bean gum (3%). The semisolids maintained the nanometric size of the particles and the PhSe2 content at around the initial concentration (1.0 mg/g). They also displayed non-Newtonian pseudo-plastic behavior and a highly mucoadhesive property. The chorioallantoic membrane method indicated the absence of hemorrhage, coagulation, or lysis. The compound, from both non-encapsulated and nano-based hydrogel delivery systems, remained on the surface of the bovine vaginal mucosa. Therefore, the formulations displayed the intended properties and could be a promising alternative for the treatment of trichomoniasis.